Formulasi dan Uji Efektivitas Sediaan Sirup Ekstrak Daun Kacapiring (Gardenia jasminoides J. Ellis) Sebagai Antipiretik Terhadap Mencit (Mus musculus L) YANG DI INDUKSI VAKSIN DPT - Firman Rezaldi; Siti Khodijah; Sumarlin US (Universitas Cokroaminoto Palopo, 2022)
Flavonoids in plate glass leaves (Gardenia jasminoides J. Ellis) can inhibit the cyclooxygenase enzyme, especially cyclooxygenase-2, which plays a role in prostaglandin biosynthesis so that the process of fever is inhibited. In addition, flavonoids and paracetamol have a similar structure. The aim of this research was to test the syrup extract of G. jasminoides leaves to have antipyretic effectiveness against male mice (Mus musculus) induced by DPT vaccine. The research method used was experimental research. The research stages were plant determination, the manufacture of G. jasminoides leaf extract using the maceration method with 96% ethanol solvent, phytochemical screening, syrup formulation with the active substance of G. jasminoides leaf extract and additives in the form of saccharose, citric acid, grape essence, propylene glycol and distilled water. Antipyretic testing was carried out in vivo, namely the male mice were measured at the initial oral temperature, then injected intramuscularly with the DPT HB vaccine in the thigh, two hours after experiencing optimum fever (above normal temperature), then each group was treated with oral method, namely negative control (syrup basis), positive control (paracetamol syrup), ethanol extract syrup from G. jasminoides leaves dose 1; 3 and 5 mg / 20gBW. The results showed that extract G. jasminoides could be formulated into syrup preparations with good physical quality in terms of organoleptic, density, volume transferred and pH. The dose of G. jasminoides leaf extract syrup 5 mg/20Gbb was the most effective dose as an antipyretic in male mice induced with DPT vaccine with a total temperature reduction of 2oC. Keywords: antipyretic, gardenia, syrup.